Long-Distance Passive Sensing Tag Design Based on Multi-Source Energy Harvesting and Reflection Amplification - Gang Li; Chong Pan; Bo Wu; Zhiliang Xu; Shihua Li; Yehua Zhang; Yongjun Yang; Zhuohang Zou; Chang Shi; Muze Wang (Micromachines)
Wireless sensor networks often rely on battery power, which incurs high costs, considerable volume, and a limited lifespan. Additionally, the communication range of existing passive sensor tags remains short, which challenges their suitability for evolving Internet of Things (IoT) applications. This paper, therefore, presents a long-distance passive RFID sensing tag that integrates multi-source energy harvesting and reflection amplification. Multi-source energy harvesting enhances tag receiving sensitivity and extends the system’s downlink communication distance, while reflection amplification increases tag reflection power and improves the uplink communication distance, thereby significantly expanding the overall communication range. The test results show that the tag achieves a receiving sensitivity of −45 dBm, a reflection gain of 44 dB, and a communication distance of up to 96 m.